Plant-Based Diets and Athletic Performance: A Critical Review of Evidence Across Endurance, Strength, and Hypertrophy Domains - Polakowska, Anna; Mazurek, Jagoda; Pyzik, Alicja; Dziegciarczyk, Anna; Mróz, Oliwia; Borkowska, Karolina (Quality in Sport, 2025)
Background: The popularity of plant-based diets among athletes has surged in recent years, initiating debate over their adequacy for sports performance. While such diets offer documented health benefits, their impact on physical performance of athletes, particularly in strength and muscle hypertrophy outcomes, remains often unclear and questioned. Objective: This review critically examines the current evidence on the effects of plant-based (vegan and vegetarian) diets on athletic performance in terms of endurance, strength, and muscle hypertrophy. Methods: A structured search of the literature from 2010 to 2025 was conducted using PubMed, Web of Science, and Scopus. Primary research papers covering physically active individuals and athletes were included if they compared plant-based and omnivorous diets and reported on at least one performance-related outcome. Data were extracted and summarised narratively by performance area. Evidence Summary: Endurance performance appears well-supported by plant-based diets, primarily due to their high carbohydrate and antioxidant content. Strength and hypertrophy outcomes show no significant differences between diet groups when total energy and protein needs are met. Modeling studies confirm that well-planned plant-based diets can deliver sufficient protein and leucine for muscle growth. Key micronutrients (e.g., B12, iron, DHA) may require supplementation. Conclusions: When adequately planned, plant-based diets can support athletic performance across a range of sports. Further longitudinal and mechanistic research is warranted, particularly among elite athletes and in strength-focused disciplines.